المفسرون الجزائريون واحتفالهم عند ختم دروسهم في تفسير القرآن الكريم - زيباني, منير (جامعة الوادي university of eloued, 2023)
هذا المقال بعنوان"المفسرون الجزائريون واحتفالهم عند ختم دروسهم في تفسير القرآن الكريم"، حيث إنّ الناظر في كتب تراجم أعلام الجزائر يرى بعض المظاهر التي تعدّ من خصائص الجزائريين دون غيرهم، خاصة عند ختمهم تفسير القرآن الكريم شفويا؛ فأحببت تدوين ذلك لبيان أحد اللوحات الفنية الأدبية والأخلاقية؛ لذا طرحت الإشكال التالي: ما هي صورة هذا الاحتفال؟ ومن هم أبرز علماء الجزائر الذين أتموا تفسير القرآن باحتفال خلده التاريخ كمظهر بارز من مظاهر التحضر؟ حيث إنني وقفت على العديد من العلماء الذين احتفلوا عند ختم القرآن، وذكرت منهم بعض النماذج في خطة بحث توافق طبيعة المقال اشتملت على مقدّمة، ومبحثين، وخاتمة. Abstract: This article is entitled "Algerian commentators and their celebration when concluding their lessons in the interpretation of the Noble Qur'an," as the beholder in the books of the translations of Algerian flags sees some aspects that are characteristic of the Algerians without others, especially when they conclude the interpretation of the Noble Qur'an orally; I liked writing it down to show one of the literary and moral paintings; So I posed the following question: What is the image of this celebration? And who are the most prominent Algerian scholars who completed the interpretation of the Qur’an with a celebration immortalized by history as a prominent aspect of civilization? Whereas, I came across many scholars who celebrated at the conclusion of the Qur’an, and I mentioned some examples of them in a research plan that corresponds to the nature of the article, which included an introduction, two chapters, and a conclusion. key words: Explanation; Celebration: seal; The Quran; Scholars; Algeria
مقال
Keywords: تفسير؛ الاحتفال: ختم؛ القرآن؛ علماء؛ الجزائر